2022
DOI: 10.1590/0034-737x202269010014
|View full text |Cite
|
Sign up to set email alerts
|

Performance of wheat varieties grown from seeds with different vigor levels

Abstract: The objective of this study was to evaluate the performance of wheat plant grown from seeds with different vigor levels. The experimental design was randomized blocks in a 3 x 3 factorial design (cultivar x vigor level) with four replications. The wheat cultivars were Tbio Toruk, Tbio Mestre and Tbio Iguaçu. The classification of vigor levels was high, medium and low, determined by several vigor procedures. The following evaluations were performed: plant height, number of spikelets in the main tiller, number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…High-vigor lots have a higher capacity to withstand an uncontrolled storage condition, becoming dependent on the genetic material compared to low-vigor lots (Koch et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…High-vigor lots have a higher capacity to withstand an uncontrolled storage condition, becoming dependent on the genetic material compared to low-vigor lots (Koch et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that seed physiological quality affected grain yield. Koch et al (2022) investigated the performance of wheat varieties from seeds with different levels of vigor and concluded that seed vigor significantly affected grain yield.…”
Section: Introductionmentioning
confidence: 99%